Improved Moisture Stability of Perovskite Solar Cells with a Surface‐Treated PCBM Layer. Issue 2 (27th December 2018) - Hangoma, Pesi Mwitumwa; Ma, Yongchao; Shin, Insoo; Liu, Yanliang; Park, Woon Ik; Jung, Yun Kyung; Lee, Bo Ram; Jeong, Jung Hyun; Park, Sung Heum; Kim, Kwang Ho
Abstract : Having achieved power conversion efficiencies higher than 22%, perovskite solar cells (PSCs) look set to be game changers in the field of photovoltaics. Their instability in humid environments, however, reduces their potential for commercialization. In this study, the role chemical degradation plays in moisture‐affected devices is investigated, and, based on this concept, a technique that enhances the device stability of p‐i‐n PSCs is developed. By surface treatment of the [6, 6]‐phenyl‐C61‐butyric acid methyl ester (PCBM) layer with hydrophobic stearic acid and ethylenediamine, increased moisture resistivity of PCBM is achieved. The treated surface of the PCBM layer improves hydrophobicity, with a contact angle of 108°, and also prevents water ingress in the perovskite layer longer than non‐treated surfaces. In addition, interfacial stability is enhanced by the suppressed interaction between the ions and the electrodes, resulting in treated devices exhibiting improved stability in their photovoltaic parameters compared to non‐treated devices when exposed to a dark environment with a relative humidity of 45%. Abstract : The surface treatment of the electron transport layer, PCBM, is done using stearic acid. The treated surface consists of perpendicularly aligned monolayers of stearic acid which repel water, creating a hydrophobic film on top of PCBM. Amide linkages which crosslink stearic acid and the methyl ester group of PCBM, act as a barrier by preventing iodine ions which migrate from the active layer, reacting with the aluminum electrode.